Understanding the status of evidence in policing research: reflections from a study of policing domestic abuse - Biddle, P. (Policing and society, 2020)
Experimentation, innovation, and evaluation are key elements of Evidence Based Policing (EBP), itself often aligned to wider efforts to improve police professionalism. Producing new evidence of ‘what works’ is an important part of the challenge of developing more effective policing responses to complex demands in a period of limited resources. Drawing on our experience of understanding successful innovations in policing domestic abuse, we reflect on the quality and status of research evidence in policing and the implications that these might have in terms of informing good practice. We worked in collaboration with police staff to identify areas in which innovation in policing domestic abuse has been successful. Selected projects were required to meet the criteria of having been developed from an evidence base (broadly defined to include professional expertise, scientific research and guidance from authoritative bodies), subject to evaluation and as having had a demonstrable positive impact. Our collaborative work identified some interesting variations in terms of understandings of these three criteria in the context of innovations in policing domestic abuse. Here we reflect on what passes as evidence and evaluation and more broadly what counts as research which helps determine what works, all as part of our project to build capacity through collaborative partnership policing